Peran Sosial Gereja Menurut Barth dan Moltmann [The Social Role of the Church according to Barth and Moltmann] - Edy J. P. Gurning (Universitas Pelita Harapan, 2019)
The ideology of the nation Indonesian is Pancasila. Within this ideology Pancasila, the state ensures religious freedom practices and provides space for religion to play a role in carrying out justice and peace in society. Particularly in the post-secular era, the role of religion becomes more significant. Post-secularism provides an active not passive and greater role for religion in presenting its social role. Christianity, as one of the religions in Indonesia, is also urged to participate in playing its social roles. Based on the characteristic Indonesian context, the social role of the church initiated by Karl Barth is far better to be employed in Indonesia than the social role of the church initiated by Jurgen Moltmann.